Effective initial treatment of diffuse pulmonary lymphangiomatosis with sirolimus and propranolol: a case report - Dimiene, Ieva; Bieksiene, Kristina; Zaveckiene, Jurgita; Andrulis, Mindaugas; Optažaite, Daiva-Elžbieta; Vaguliene, Neringa; Zemaitis, Marius; Miliauskas, Skaidrius (Medicina, 2021)
Diffuse pulmonary lymphangiomatosis (DPL), an exceptionally rare disease, mainly occurs in children and young adults of both sexes. Even though DPL is considered to be a benign disease, its prognosis is relatively poor. Because of its rarity, little guidance on diagnosis and treatment is available, which makes working with patients with DPL challenging for clinicians. We present here a case of a young man with DPL in whom treatment with sirolimus and propranolol rapidly achieved positive radiological and clinical effects.